2017
DOI: 10.1007/s10555-017-9656-2
|View full text |Cite|
|
Sign up to set email alerts
|

Combining forces: the promise and peril of synergistic immune checkpoint blockade and targeted therapy in metastatic melanoma

Abstract: Both immune checkpoint inhibitors and molecularly targeted agents have dramatically improved clinical outcomes for patients with metastatic melanoma. These two therapeutic approaches harness distinct mechanistic pathways-on the one hand, monoclonal antibodies against the immune checkpoints CTLA-4 and PD-1/PD-L1 stimulate the T cell mediated host immune response, while targeted inhibitors of the proto-oncogenes BRAF and MEK disrupt constitutive kinase activity responsible for tumor growth. The prospect of combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…Melanoma is one of the most threatening malignancies and has high metastatic potential. Although in the recent years, significant progresses have been made in melanoma treatment with the appearance and widespread application of the combinational immunotherapy [1][2][3][4], it is still necessary to explore other treatment options to get better clinical output because the response rates to immunotherapy are not 100%. This might be mainly due to that the antigens selected for these approaches do not cover the full spectrum of melanoma cells present in a tumor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is one of the most threatening malignancies and has high metastatic potential. Although in the recent years, significant progresses have been made in melanoma treatment with the appearance and widespread application of the combinational immunotherapy [1][2][3][4], it is still necessary to explore other treatment options to get better clinical output because the response rates to immunotherapy are not 100%. This might be mainly due to that the antigens selected for these approaches do not cover the full spectrum of melanoma cells present in a tumor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] Studies have begun to investigate the extent to which combination therapies pose clinical safety and tolerability challenges, and whether these challenges will limit their usefulness as anticancer therapy. [46][47][48][49] The only current FDA-approved regimen using combined ICI therapy is nivolumab plus ipilimumab for treating advanced melanoma, RCC, or microsatelliteunstable tumors. 50,51 Nivolumab plus ipilimumab resulted in enhanced survival outcomes compared with ipilimumab monotherapy in advanced melanoma.…”
Section: Ctla-4mentioning
confidence: 99%
“…Controversy exists over the impact of adding MAPK pathway inhibitors to ICIs. While several preclinical studies initially reported that MAPK inhibitors can positively modulate the immune microenvironment (114), more recent data have demonstrated that PD-1-resistant melanomas have a transcriptional signature consistent with innate anti-PD-1 resistance (IPRES), defined as having upregulation of genes modulating mesenchymal transition, cell adhesion, angiogenesis, and extracellular matrix remodeling. This IPRES signature is very similar to that induced by combined BRAF/MEK or BRAF inhibition, suggesting that these drugs may mediate resistance to anti-PD-1 (81).…”
Section: Targeted Agentsmentioning
confidence: 99%